Association between vaccination uptake, vaccine type, and long COVID in rural Indonesia - Sujarwoto, Sujarwoto; Holipah, Holipah; Andarini, Sri; Aknuranda, Ismiarta; Sahputri, Rindi A. M.; Sarwono, Achwan; Kusharyanto, Paulus Gatot; Kusumo, Budiarto Eko; Maharani, Asri (Frontiers in Public Health, 2025)
IntroductionLong COVID affects a significant proportion of individuals after SARS-CoV-2 infection. While vaccines reduce severe disease, their effect on long COVID remains unclear, especially in rural, resource-limited settings. This study investigates the association between vaccination status, vaccine type, and long COVID in Malang Regency, East Java.MethodsWe analysed cross-sectional data from 5,735 adults who tested positive for COVID-19 between June 2022 and June 2023. Long COVID was defined as persistent symptoms ≥12 weeks post-infection. Data on vaccination status, vaccine type, comorbidities, and sociodemographic characteristics were collected through surveys and linked to immunisation records. Multivariable logistic regression was used to estimate adjusted odds ratios (aORs) for long COVID, including stratified analyses by vaccine platform and dose.ResultsLong COVID was reported by 56.2% of participants. Compared to unvaccinated individuals, those who received mRNA vaccines had significantly lower odds of long COVID, Moderna (OR = 0.341, 95% CI: 0.067–0.887) and Pfizer (OR = 0.220, 95% CI: 0.057–0.771), while recipients of non-mRNA vaccines, such as Sinovac (OR = 1.205, 95% CI: 1.038–1.331), had increased odds. A dose–response relationship was observed for mRNA vaccines, with two doses (OR = 0.420, 95% CI: 0.402–0.511) and three or more doses (OR = 0.743, 95% CI: 0.601–0.712) both reducing risk compared to no mRNA vaccination. Older age, hypertension, higher education, and higher income were also associated with increased long COVID risk.ConclusionmRNA COVID-19 vaccines and full vaccination schedules are strongly protective against long COVID in rural Indonesia. These findings highlight the need to improve access to mRNA vaccines and booster doses to reduce long-term COVID-19 impacts in underserved populations.